The credit card system as a part of international payment system system : creation development, practice and the movement towards legal harmonization in the European Community and Turkey - Aydınöz, Aslı (My University, 1993)
unknown
Keywords: A.E.T.-KREDİ KARTLARI; BANKACILIK-KREDİ KARTLARI